Varenicline: For smoking cessation - Rao, J; Shankar, PK (Kathmandu University Medical Journal, 2010)
Varenicline, a partial agonist of α4β2 nicotinic acetylcholine receptor (nAChR), is the most recently approved drug for smoking cessation. Despite the availability of effective treatments for smoking cessation, such as nicotine replacement therapy and Bupropion sustained-release, abstinence rates remain less than optimal. As a nAChR partial agonist, Varenicline attenuates the craving and withdrawal symptoms that occur with abstinence from nicotine and also reduces the rewarding effects of nicotine obtained from smoking in patients who lapse. Clinical trials have demonstrated superior efficacy of this drug over Bupropion-SR for achieving abstinence from smoking, and Varenicline has also been shown to significantly delay smoking relapse. As the latest agent approved for smoking cessation, the mechanism of action, efficacy, and safety of Varenicline has been reviewed in this paper. Key words: α4β2 nicotinic acetylcholine receptor; Varenicline; smoking cessation; partial agonist. DOI: 10.3126/kumj.v7i2.2714 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26, 162-164